ASSESSMENT OF TERTIARY EDUCATION TRUST FUND IN ACHIEVING THE PROVISION OF FACILITIES IN PUBLIC UNIVERSITIES IN AKWA-IBOM STATE (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study assessed the extent of Tertiary Education Trust Fund (TetFund) in achieving the provisions of facilities in public Universities in Akwa Ibom. Three Objectives, Three Research Questions and Three Hypotheses guided the Study. The study adopted a descriptive survey research design. A sample of 235 respondents which comprised 12 Principal Officers and 223 lecturers were used for the study. The study adopted a multi-staged sampling procedure. The instrument for data collection was a 30-item questionnaire titled: Assessment of Tetfund Infrastructural Provision Questionnaire (ATIPQ). The copies of the instrument were validated by three experts, two in Educational Administration and Planning and one from measurement and evaluation, all in College of Education, Michael Okpara University of Agriculture, Umudike, Abia State. Cronbach Alpha statistic was used to determine the internal consistency of the instrument which yielded 0.89 coefficient. Three briefed research assistants helped in the administration and collection of the instrument. Out of 235 copies of the questionnaire administered, 219 copies representing 93 percent return rate were used for data analysis. Mean and standard deviation was used to answer the five research questions raised for the study while t-test statistic was used to test the three null hypotheses raised for the study at 0.05 level of significance. The findings showed among others that Tetfund provided infrastructural facilities such as Classroom facilities and Library facilities, to a low extent while it provided ICT facilities to a very low extent. Based on the findings, the study therefore recommended among others that Tetfund should adequately provide classroom facilities to Public Universities especially those ones that suffer gross lack of facilities. It was equally recommended that Government should make more funds available to TetFund to enable the agency provide adequate facilities to Public Universities.